PERUMUSAN VISI, MISI, TUJUAN DAN PROGRAM PAUD DI TKIT SALSABILA AL-MUTHI'IN YOGYAKARTA - Suhaini (STPI Bina Insan Mulia Yogyakarta, 2020)
This study aims to find out how the formulation of vision, mission, goals and program of PAUD TKIT Salsabila AL-Muthi’in Yogyakarta. This research is a qualitative descriptive study that describes real or direct of what is found in the field. The techniques used to collect research data are observation, interviews, and documentation. The results of this study indicate that in the formulation and determination of the vision, mission, objectives and programs at TKIT Salsabila al-Muthi'in carried out through deliberation meetings involving the entire stackholder of PAUD institutions. This is done so that the vision, mission, goals and programs that are formulated can represent the wishes of all the PAUD institutions. The formulation of the vision and mission, objectives and programs are formulated in accordance with the indicators to be achieved by the institution based on Early Childhood Education Standards.